Psychodynamic Therapists’ Rating of the Most Important Technical Guidelines to Follow When Interpreting Defenses In-Session - Bhatia, Maneet; Petraglia, Jonathan; de Roten, Yves; Drapeau, Martin (Canadian Journal of Counselling and Psychotherapy, 2019)
In this study, we attempted to gain an understanding of the attitudes of practicing psychodynamic therapists on the importance of clinical principles regarding the interpretation of defenses in session. We asked 140 psychodynamic psychotherapists to complete a survey to determine their level of agreement with and ranking of these clinical principles. Results of the survey indicated that therapists strongly agreed with the importance of the clinical principles. When examining therapists’ ranking of the principles three groups emerged (high, middle, and low). Clinical implications of these findings and directions for future research are explored.